Hacia una propuesta integradora de sistemas basados en conocimiento y de descubrimiento - Rancan, Claudio (2006)
This paper proposes a system architecture for integrating knowledge discovery and knowledge based systems.\nSome considerations on the development viability of the associated system are drawn based on the involved technologies maturity.